Usability Testing on Desktop-based Operating Systems with University Users - Ronaldo Muyu, Christy Poluakan, Undap E.B Yeremia (JR Education, 2021)
The operating system is the most important computer system software. Currently, there are several operating systems that are so popular, including Windows and MacOS. Usability measurements were made between the Windows and MacOS operating systems. This study aims to measure the comparison of usage between Windows and Mac operating systems in lectures at Manado State University. In this study using a questionnaire with 13 questions asked and 25 respondents received, then analyzed the data using a Guttman measuring scale. The results show that the Windows operating system is more widely used with a much higher percentage than MacOS. The results of this study also prefer the Windows operating system with 84.61% while MacOS with 11.38%. Because from the point of view of popularity among Manado University students, many use Windows because it is considered easier and the applications provided for free are different from the prepaid MacOS.